2021
DOI: 10.1021/acs.jpclett.1c03295
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical Impact of Lipid A Modification Caused by Mobile Colistin Resistance Gene on Bacterial Outer Membranes

Abstract: Expression of mobile colistin resistance gene mcr-1 results in the addition of phosphoethanolamine (pEtN) to the lipid A headgroup in the bacterial outer membrane (OM) of Gram-negative bacteria, increasing the resistance to the last-line polymyxins. However, the potential biological consequences of such modification remain unclear. Using coarse-grained molecular simulations with quantitative lipidomics models, we discovered pEtN modification of the lipid A headgroup caused substantial changes to the morphology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Several lines of evidence supported this conclusion. First, to clarify the mechanism of the MCR-1-mediated OM permeability defect, we initially hypothesized that pEtN modification of lipid-A damaged OM, because the overexpression of MCR-1 caused substantial changes to the morphology and physicochemical properties of the OM [ 52 ]. However, the OM permeability was not restored in E. coli E246A, an MCR-1 mutant without pEtN transferase activity.…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence supported this conclusion. First, to clarify the mechanism of the MCR-1-mediated OM permeability defect, we initially hypothesized that pEtN modification of lipid-A damaged OM, because the overexpression of MCR-1 caused substantial changes to the morphology and physicochemical properties of the OM [ 52 ]. However, the OM permeability was not restored in E. coli E246A, an MCR-1 mutant without pEtN transferase activity.…”
Section: Discussionmentioning
confidence: 99%
“…Lipid A modification is a known resistance mechanism for colistin resistance . Because HSD1624 and 1625 were able to potentiate colistin, in colistin-resistant Gram-negative bacteria, we wondered if the compounds were causing sensitization via lipid A modification.…”
Section: Resultsmentioning
confidence: 99%
“…Lipid A modification is a known resistance mechanism for colistin resistance. 30 Because HSD1624 and 1625 were able to potentiate colistin, in colistin-resistant Gram-negative bacteria, we wondered if the compounds were causing sensitization via lipid A modification. Matrix-assisted laser desorption/ionization (MALDI)−time of flight (ToF) analysis of lipid A was carried out to determine if there was any change in either the phosphoethanolamine (PetN) or aminoarabinose (Ara4N) content on the lipid A anchor of the LPS component of the bacterial outer membrane in the most re-sensitized colistin-resistant strain (P. aeruginosa TRPA161).…”
Section: Lipid a Analysis Of Trpa161 By Maldi-tof Mass Spectrometrymentioning
confidence: 99%
“…MCR-1, ArnT and diacylglycerol kinase A (DgkA)]. The interactions of colistin with lipid model membranes have been described thoroughly by structural biology studies ( 48 ), which have shown how these interactions change when pEtN is added to the phosphate groups of lipid A ( 49 , 50 ) and how changes in LPS charge renders polymyxins ineffective. Therefore, in theory, for polymyxins to regain their efficacy these changes need to be prevented.…”
Section: Promising Targets In Lipid a Structural Modification Systems...mentioning
confidence: 99%